"Go forth and wrestle with the legal system": Some perceptions and experiences of lesbian parents in rural Australia. Issue 1 (26th March 2018) - Bacchus, Ruth
Abstract: This study explores the perceptions and experiences of a small group of lesbian parents living in rural Australia, who discussed the decisions they made in creating their families, their expectations and understanding of their roles and relationships and their concepts of family and parenthood. The study also explores how these lesbian‐parented families have negotiated the complex legal frameworks under which they exist.